Robotic-assisted paraesophageal hernia repair: a case-control study - Gehrig, Tobias; Mehrabi, Arianeb; Fischer, Lars; Kenngott, Hannes Götz; Hinz, Ulf; Müller, Beat P. (Langenbeck's archives of surgery, 2013)
AimsThe da Vinci® telemanipulation system offers a wide range of precise movements and 3D visualization with depth perception and magnification effect. Such a system could be useful for improving minimally invasive procedures—as in the case of large hiatal hernia with paraesophageal involvement (PEH) repair. Studies reporting on the robotic-assisted PEH repair are scarce, and a comparison to the standard operation techniques is lacking. Therefore, we decided to investigate the feasibility and safety of robotic-assisted surgery (RAS) compared to conventional laparoscopic (CLS) and open surgery (OS) for the first time.MethodsWe investigated 42 patients for the perioperative outcome after PEH repair. Twelve patients were operated on with RAS, 17 with CLS, and 13 with OS. Operating time, intraoperative blood loss, intra- and postoperative complications, mortality, and duration of hospital stay were analyzed in each method.ResultsOn average, operating time in the RAS group was 38 min longer, and the intraoperative blood was loss 217 ml lower compared to OS. Both results were similar to the CLS group. The intraoperative complication rate was similar in all groups. The postoperative complication rate in the RAS group was significantly lower than the OS group, though again similar to the CLS group. The hospital stay was 5 days shorter in the RAS group than the OS group and once again similar to the CLS group.ConclusionThe results show that RAS is feasible and safe. It appears to be an alternative to OS due to lower intraoperative blood loss and potentially fewer postoperative complications, as well as shorter hospital stay. Though, RAS is not superior to CLS.